Sports and competition law in South Africa: the need to account for the uniqueness of sport when applying the competition Act 89 of 1998 to the sports industry - Sun, Huajun (Rhodes University, Faculty of Law, Law, 2017)
Regulation of sport as an economic activity has become increasingly prevalent in a number of foreign jurisdictions. This thesis considers the applicability of competition law to the sports industry from a South African perspective. Although the Competition Act 89 of 1998 is yet to be applied in the context of organisation of professional sport, the sector is not free from the scrutiny of competition law authorities. It is necessary to subject sports organisers and governing bodies to competition law in order to ensure that their administrative powers, which effectively place them in positions of market dominance, are not misused for their own commercial interests. On the other hand, the unique characteristics of sports should also be taken into account when applying competition law to the sector. In particular, it should be noted that sporting activities are not purely economic in nature, and that they are also conducted in order to achieve various social objectives. This thesis examines foreign jurisprudence that have dealt with the relevance of purely sporting justifications under competition law, and conclude that South Africa law should take into account the unique nature of sport when determining whether a conduct should be per se prohibited under the Competition Act, as well as when the rule-of-reason enquiry is conducted. This would require an amendment to the Act, a draft of which is proposed in this thesis. Finally, the proposed approach is applied in the context of the player transfer rules in football, in order to highlight problematic aspects of the transfer system even when considered in light of the unique nature of sports.
Keywords: Uncatalogued